2014
DOI: 10.1155/2014/621437
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness and Cardiovascular Therapy

Abstract: The world population is aging and the number of old people is continuously increasing. Arterial structure and function change with age, progressively leading to arterial stiffening. Arterial stiffness is best characterized by measurement of pulse wave velocity (PWV), which is its surrogate marker. It has been shown that PWV could improve cardiovascular event prediction in models that included standard risk factors. Consequently, it might therefore enable better identification of populations at high-risk of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
103
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 130 publications
(137 reference statements)
0
103
0
5
Order By: Relevance
“…Previous meta-analyses have shown that antihypertensive agents of different classes may influence arterial stiffness and wave reflections to different extents, as summarized in Table 1 (2)(3)(4)(5). The results of the meta-analysis of Chen and co-authors add to previous evidence by specifically focusing on ARBs' effect and on AIx.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Previous meta-analyses have shown that antihypertensive agents of different classes may influence arterial stiffness and wave reflections to different extents, as summarized in Table 1 (2)(3)(4)(5). The results of the meta-analysis of Chen and co-authors add to previous evidence by specifically focusing on ARBs' effect and on AIx.…”
mentioning
confidence: 69%
“…In addition, ARBs contrast the profibrotic action of the renin-angiotensin system, reducing the collagen content of the arteries and attenuating extracellular matrix remodeling, and they may reverse smooth muscle hypertrophy, increasing arterial distensibility (6). Such mechanisms are plausible and they have been documented in a number of studies (4). Unfortunately, in their metaanalysis Chen and coworkers do not provide data on the pressor effect of the antihypertensive drugs at the brachial artery level, and even more so at the aortic (central) level.…”
mentioning
confidence: 99%
“…However, current non-invasive measures of arterial stiffness are BP-dependent, making it hard to distinguish the beneficial BP-lowering effects from those caused by de-stiffening of the arterial wall. In addition to BP-lowering drugs, statins, antidiabetic drugs, advanced glycation end-products, cross-link breakers, and anti-inflammatory drugs have been proposed to lower arterial stiffness, but are still under development or validation [80]. On the other hand, favourable effects of physical activity [81][82][83][84][85] and weight reduction [86] on arterial stiffness have been described in both healthy individuals and in patients with cardiovascular risk factors.…”
Section: Antihypertensive and De-stiffening Strategies For Heart Failmentioning
confidence: 99%
“…Promising results have been obtained with anti-inflammatory drugs such as tumor necrosis factor-α inhibitors, matrix metalloproteinase inhibitors, elastase inhibitors, and collagen crosslink breakers in preclinical studies. 12,13 However, experience in humans is limited, and results from human trials have been mixed. 12 Reducing blood pressure is proven to reduce arterial stiffening, and some antihypertensive drugs acting on the renin-angiotensin-aldosterone axis may have specific blood pressure-independent antistiffening effects.…”
Section: May 19 2015mentioning
confidence: 99%